Vertical dynamic patterns of Vibrio spp. in the northwestern Pacific Ocean - Jeeny, Leihaothabam; Huang, Keyi; Chen, Xing; Wang, Yan; Zhu, Shaodong; Zhang, Yulin; Zhang, Xiao-Hua; Wang, Xiaolei (Frontiers in Microbiology, 2025)
In marine ecosystems, Vibrio species are as they facilitate nutrient cycling and impact the condition of marine life. To understand their ecological dynamics and how they adapt to various environmental situations, this study examined the vertical distribution pattern and assembly processes of Vibrio species across a depth gradient (5–6000 m) within the Kuroshio Extension in the Northwest Pacific Ocean. Through quantitative PCR and high-throughput sequencing based on 16S rRNA genes, the abundance of Vibrio spp. showed a strong vertical stratification. Vibrio community compositions varied significantly among the ocean surface mixed layer (5-105 m, UL), the pycnocline and North Pacific Intermediate Water layer (155-700 m, ML), and bathypelagic layer (>1000 m, BL), which was reflected by a strong vertical depth decay pattern. In the UL, Vibrio sagamiensis, Paraphotobacterium marinum, V. caribbeanicus, V. campbellii and Photobacterium phosphoreum were the dominated species. V. pomeroyi was the most abundant species in ML and BL, and V. sagamiensis, P. marinum and P. phosphoreum usually persisted in deeper water layers, reflecting their potential adaptations to deep ocean conditions. Both deterministic factors (e.g., temperature, salinity, dissolved oxygen, NO3−, PO43− and SiO32−) and stochastic processes shaped Vibrio community assembly mechanism, with stochasticity dominating community structure in UL and heterogeneous selection playing a key role in ML and BL. Our findings highlight the complex interplay between environmental gradients and stochasticity in shaping Vibrio communities along the depth in the water column, contributing to a deeper understanding of their dynamics in the open ocean.